Accumulation and evolution of ice jams influenced by different ice discharge: An experimental analysis - Chen, Pangpang; Cheng, Tiejie; Wang, Jun; Cao, Guangxue (Frontiers in Earth Science, 2023)
Ice jam, a unique hydrological phenomenon of rivers in cold regions, is an important cause of ice flood. There are many harms of ice jam: blocking the water flow section, causing the water level to rise, inundating farmland and houses, damaging hydraulic structures, and interrupting shipping. The formation of ice jam is influenced by various factors in different fields. The accumulation of ice jam is a complex process worthy of studying. However, the previous studies were seldom taking account of ice discharge factors. This study carries out 29 tests on the accumulation of ice jam, and discovers 4 kinds of phenomena: inlet ice failing to submerge (case 1), thickening from upstream to downstream (case 2), thickening from downstream to upstream (case 3), and failing to form ice jam (case 4). Two typical examples were used to detail cases 2 and 3. Through mechanical analysis, the authors suggested differentiating between the two cases by the longitudinal boundary line running through the point of Froude number (Fr)=0.119. Further, the authors analyzed the phenomena where it is difficult to form ice jam, and suggested using the critical discriminant line to distinguish between cases 3 and 4. Combined with the longitudinal boundary line, a partition result diagram of different accumulation features of the ice jam was presented to differentiate between the four accumulation phenomena of ice jam.